Unravelling the ambivalent motivational power of gamification: A basic psychological needs perspective. Issue 127 (July 2019) - van Roy, Rob; Zaman, Bieke
Highlights: Self-Determination Theory is useful to understand, research and design gamification. Game elements can both support and hinder basic psychological need satisfaction. Situational factors shape people's perception of game elements. Transferring a game element to non-game contexts can drastically change its meaning. Abstract: Previous research on the interaction with game design elements in an educational setting has presented both desirable and undesirable outcomes but misses out on a theoretical and empirical explanation of the underlying psychological processes at work when interacting with gamified systems. This article aims at gaining an in-depth understanding of the power of gamification as shaping motivation based on the principles of basic psychological need satisfaction derived from Self-Determination Theory. This study is based on the qualitative analysis of 125 surveys ( n = 40) and 2 focus group interviews ( n = 7) gained throughout a 15-week university master course in which students voluntary interacted with a gamified platform. The results show the ambivalent motivational power of game elements in technology-supported learning environments—affording feelings of autonomy, competence and relatedness in some cases, thwarting them in others—with situational factors playing an important role in this process. These findings aid in understanding the workings of gamification and might help in explaining the mixed results about the effectiveness of gamification reported in previous literature. Conclusions and avenues for future research are reported.